Metabolic complications in acromegaly after neurosurgery: a meta-analysis. Issue 6 (December 2020) - Cozzolino, Alessia; Feola, Tiziana; Simonelli, Ilaria; Puliani, Giulia; Hasenmajer, Valeria; Minnetti, Marianna; Giannetta, Elisa; Gianfrilli, Daniele; Pasqualetti, Patrizio; Lenzi, Andrea; Isidori, Andrea M
Abstract : Objective: Neurosurgery is the first-line treatment for acromegaly. Whether metabolic disorders are reversible after neurosurgery is still debated. The meta-analysis aimed to address the following questions: (i) Does neurosurgery affect glycolipid metabolism? (ii) Are these effects related to disease control or follow-up length? Design: A meta-analysis and systematic review of the literature. Methods: Three reviewers searched databases until August 2019 for prospective trials reporting glycometabolic outcomes after neurosurgery. Three other extracted outcomes, all assessed the risk of bias. Results: Twenty studies were included. Neurosurgery significantly reduced fasting plasma glucose (FPG) (effect size (ES): −0.57 mmol/L, 95% CI: −0.82 to −0.31; P < 0.001), glucose load (ES: −1.10 mmol/L, 95% CI: −1.66 to −0.53; P < 0.001), glycosylated haemoglobin (HbA1c) (ES: −0.28%, 95% CI: −0.42 to −0.14; P < 0.001), fasting plasma insulin (FPI) (ES: −10.53 mU/L, 95% CI: −14.54 to −6.51; P < 0.001), homeostatic model assessment of insulin resistance (HOMA-IR) (ES: −1.98, 95% CI: −3.24 to −0.72; P = 0.002), triglycerides (TGDs) (ES: −0.28 mmol/L, 95% CI: −0.36 to −0.20; P < 0.001) and LDL-cholesterol (LDLC) (ES: −0.23 mmol/L, 95% CI: −0.45 to −0.02 mmol/L); P = 0.030) and increased HDL-cholesterol (HDLC) (ES: 0.21 mmol/L, 95% CI: 0.14 to 0.28; P < 0.001). Meta-regression analysis showed that follow-up length – not disease control – had a significant effect on FPG, with the greatest reduction in the shortest follow-up (beta = 0.012, s.e. = 0.003; P = 0.001). Conclusions: Neurosurgery improves metabolism with a significant decrease in FPG, glucose load, HbA1c, FPI, HOMA-IR, TGDs, and LDLC and increase in HDLC. The effect on FPG seems to be more related to follow-up length than to disease control.